Non-verbal Adaptation to the Interlocutors' Inner Characteristics: Relevance, Challenges, and Future Directions - Carrard, Valerie (Frontiers in Psychology, 2021)
Human diversity cannot be denied. In our everyday social interactions, we constantly experience the fact that each individual is a unique combination of characteristics with specific cultural norms, roles, personality, and mood. Efficient social interaction thus requires an adaptation of communication behaviors to each specific interlocutor which one encounters. This is especially true for nonverbal communication that is more unconscious and automatic than verbal communication. Consequently, nonverbal communication needs to be understood as a dynamic and adaptive process in the theoretical modelling and study of social interactions. This perspective paper presents relevance, challenges, and future directions for the study of nonverbal adaptation in social interactions. It proposes that nonverbal adaptability is more pertinently studied as adaptation to interlocutor's inner characteristics (i.e. expectations or preferences) than to interlocutor's behaviors per se, because behaviors are communication messages that individuals interpret in order to understand their interlocutors. The affiliation and control dimensions of the Interpersonal Circumplex Model are proposed as a framework to measure both the interlocutors' inner characteristics (self-reported) and the individuals' nonverbal responses (external coders). These measures can then be compared across different interactions to assess an actual change in behavior tailored to different interlocutors. These recommendations are proposed in the hope of generating more research on the topic of nonverbal adaptability. Indeed, after having gathered the evidence on average effects of nonverbal behaviors, the field can go further than a "one size fits all" approach, by investigating the predictors, moderators, and outcomes of nonverbal adaptation to the interlocutors' inner characteristics.